Effect of feeding levels on body weight changes, milk production and calving-conception interval of dairy cows under tropical conditions - Franco Chicco, Claudio; Godoy, Susmira; Obispo, Nestor Enrique (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
To determine the effect of low (L), medium (M) and high (H) feeding levels on body weight (BW) changes, milk production and calving-conception interval, a total of 108 dairy cows, 54 Brown Swiss (BS) and 54 Holstein (HF) were divided each in two groups according to their parturition condition, primiparous (PP) and multiparous (MP) and assigned to three experimental diets, individually provided. Rations consisted of a combination of green chopped forage (Sorghum vulgare), with 6.4% crude protein (CP) and 49% total digestible nutrients (TDN), and a supplement containing 18% CP and 75% TDN, to obtain diets approximately similar to 80 (L), 100 (M) and 120% (H) of the 1989 Nation Research Council (NRC) nutrient requirements. The experiment was carried out during 8 weeks prior calving and 22 weeks post-partum, in a 2x2x2x3 factorial arrangement. Breed (HF and BS) were considered to be the main plot and parturition conditions (PP and MP), feeding periods (pre- and post-partum periods), and diets (L, M and H feeding levels) were respectively assigned to a split-split-split plot arrangements. Rations were adjusted weekly according to body weights (BW) and milk production. Prior calving, BW of MP and PP were 539 Ó 18.3 and 489 Ó 15.2 kg, respectively. During post-partum MP and PP lost 3.8 Ó 0.48 and 4.9 Ó 0.66% BW (P < 0.05). Multiparous cows produced more milk (P < 0.05) than PP (11.3 Ó 1.4 vs. 10.5 Ó 1.4 kg) and HF more (P < 0.05) than BS (12.2 Ó 1.5 vs. 9.6 Ó 0.59 kg). Pre- and post-partum feeding regimes influenced (P < 0.05) milk production, averaging 10.5 and 9.8, 11.0 and 11.2 and 11.2 and 11.7 kg/day, respectively for feeding periods and L, M and H feeding levels. Multiparous cows had a daily intake of 5.2 Ó 1.4 kg concentrate and PP 4.9 Ó 1.6 kg. Significant regressions (P < 0.05) of concentrate intake vs milk production were: y= 6.735 + 0.878x and y= 8.125 + 0.484x, respectively for MP and PP. Cows were also influenced by breed, being the effect greater (P < 0.05) in HF than in BS. Time intervals between calving and conception independently of feeding regimes, indicate that BS animals had a shorter intervals than HF (162.1 vs 197.5 days) and MP performed better (P < 0.05) than PP (197.5 vs 262.6 days). Nutritional levels also affected calving to conception interval. This value was particularly improved in HF breed. It is concluded that feeding level during pre- and post-calving periods influences milk production, weights and calving-conception interval.